THE TRANSFORMATION OF IJTIHAD AND FATWA IN THE ERA OF ARTIFICIAL INTELLIGENCE: AN EPISTEMOLOGICAL AND TECHNOLOGICAL STUDY - Rego, Dipalpa; Samad, Duski; Firdaus (As-Sulthan Journal of Education, 2025)
The rise of Artificial Intelligence (AI) has significantly influenced Islamic legal reasoning, particularly in data processing, textual analysis, and the acceleration of jurisprudential decision-making. This study examines how AI reshapes methodological approaches to ijtihād, redefines the authority of fatwa institutions, and interacts with the epistemological foundations of Islamic law. Employing a qualitative method through literature review, the research engages classical usūl al-fiqh texts and contemporary works on AI and Islamic ethics. The findings reveal that AI acts as an assistant to ijtihād by enhancing analytical efficiency, yet it cannot replace human jurists due to its inability to comprehend maqāṣid, moral judgement, and socio-cultural context. The study also identifies the need for a “collective AI-assisted ijtihād model” to maintain accuracy, objectivity, and normative legitimacy. It concludes that AI must operate within the framework of maqāṣid al-sharīʿah and digital ethics to ensure that fatwas remain valid, adaptive, and accountable.